2008
DOI: 10.1007/s10578-008-0119-4
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Theory of Mind and Executive Function in a Sample of Children from Mainland China

Abstract: To explore the relationship between theory of mind (ToM) and executive function (EF) in a sample of individuals from mainland China, 20 children with autism spectrum disorders (ASD), 26 children with Attention Deficit Hyperactivity Disorder (ADHD), and 30 normal control subjects were compared on two batteries of ToM tasks and EF tasks. Children with ASD had a significant theory of mind impairment relative to the other controls, while non-verbal IQ removed group differences in executive function. ToM was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 50 publications
(66 reference statements)
4
29
0
6
Order By: Relevance
“…Results showed small but significant concurrent correlations in the expected directions between all studied EF subcomponents (attention shifting, WM updating and inhibition) and ToM. In line with previous research (Perner et al, 2002; Yang et al, 2009; Calderon et al, 2010), better abilities in executive control of thought or action were related to better understanding of others’ mental states at t1 (6–11 years) and t2 (7–12 years). Second, we explored whether each EF subcomponent at t1 predicted ToM at t2, or vice versa, over a 1-year period.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Results showed small but significant concurrent correlations in the expected directions between all studied EF subcomponents (attention shifting, WM updating and inhibition) and ToM. In line with previous research (Perner et al, 2002; Yang et al, 2009; Calderon et al, 2010), better abilities in executive control of thought or action were related to better understanding of others’ mental states at t1 (6–11 years) and t2 (7–12 years). Second, we explored whether each EF subcomponent at t1 predicted ToM at t2, or vice versa, over a 1-year period.…”
Section: Discussionsupporting
confidence: 87%
“…For instance, it has been found that the EF–ToM relationship extends to children between 4 1 / 2 and 6 1 / 2 years for second-order false-belief tasks and more demanding EF tasks (Perner et al, 2002). Similar results have been reported for children of middle childhood (Yang et al, 2009; Calderon et al, 2010) and in adolescents (Vetter et al, 2013). However, results in a sample of 8 1 / 2 year-olds with and without attention deficit hyperactivity disorder (ADHD) were less conclusive (Charman et al, 2001).…”
Section: Introductionsupporting
confidence: 89%
“…An important and unexplored question is related to the functional link between ToM and EF in ASD and ADHD. To the best of our knowledge, in the only study that analyzed this question, carried out by Yang et al (2009), the data from the correlational analyses showed that only inhibition was significantly related to ToM performance after partialling out non-verbal intelligence. Yang et al (2009) applied laboratory neuropsychological tasks to measure EF.…”
Section: Introductionmentioning
confidence: 92%
“…The analysis of the 11 studies that have compared children and adolescents with ASD and ADHD (see Table 1) shows that these two disorders share difficulties in social cognition, both on different levels of ToM tasks and on tests of emotion recognition (Buitelaar et al, 1999; Adachi et al, 2004; Downs and Smith, 2004; Sinzig et al, 2008; Yang et al, 2009; Bühler et al, 2011; Demurie et al, 2011; Demopoulos et al, 2013; Baribeau et al, 2015; Hutchins et al, 2016) or empathic capacity (Dyck et al, 2001). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation